CA / MWCNTs / PANI electromagnetic shielding film and preparation method thereof
By co-spinning CA with MWCNTs, and PANI nanoparticles are grown through in situ polymerization to construct a three-dimensional conductive network structure, the problem of poor conductivity of CA films is solved, and the electromagnetic shielding efficiency and mechanical properties are significantly improved.
Patent Information
- Application Number
- CN202510163557.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-05-09
AI Technical Summary
A single cellulose acetate (CA) film cannot have excellent conductivity, resulting in poor performance in electromagnetic shielding applications.
CA and multi-walled carbon nanotubes (MWCNTs) are co-spinned by electrospinning technology to form a CA/MWCNTs fiber network, and polyaniline (PANI) nanoparticles are grown through in-situ polymerization, and coated on the surface of CA/MWCNTs fibers to construct a three-dimensional conductive network structure.
It significantly improves the conductivity and mechanical properties of the film, enhances the electromagnetic shielding efficiency, and can more effectively lose the energy of electromagnetic waves, and is suitable for more complex electromagnetic protection application scenarios.
Smart Images

Figure CN119956612A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electromagnetic wave shielding materials, and in particular to a CA / MWCNTs / PANI electromagnetic shielding film and a preparation method thereof. Background Art
[0002] With the advent of the "5G" era, various electronic devices are rapidly updated, bringing great convenience to people's work and life. However, the electromagnetic energy emitted and radiated by a large number of electronic and electrical equipment constitutes an extremely complex electromagnetic environment, causing great harm to wireless devices, precision instruments, military security, etc. Long-term exposure to electromagnetic radiation will also affect the human nervous system. Therefore, electromagnetic protection has evolved into one of the fields that cannot be ignored, and the development of electromagnetic interference (EMI) shielding materials occupies a pivotal position.
[0003] Electromagnetic shielding films have the advantages of light weight, thin thickness, and flexibility. They can meet a wide range of complex application environments and ensure the normal operation of precision device modules and equipment. Among them, polymers have good corrosion resistance and thermal stability and are often used as the matrix of film materials. Among many polymers, cellulose has a unique three-dimensional cross-linked porous structure and rich functional groups; cellulose acetate (CA), as the acetate of cellulose, its acetylation process improves the resistance of CA film to mechanical stress and also increases the heat resistance of the film. However, a single CA film cannot have excellent conductivity and cannot be directly used for electromagnetic shielding. There is an urgent need to overcome the problem of poor conductivity of CA films in order to better utilize their unique amorphous structure and mechanical properties to meet the complexity of electromagnetic shielding application scenarios.
[0004] As a highly flexible process for obtaining nanofiber structures, electrospinning can obtain nanofiber materials with diverse structures by adjusting precursors, controlling experimental parameters, and nozzle structures. The spinning fibers filled with multi-walled carbon nanotubes (MWCNTs) have stronger mechanical properties and also enhance the electron transport capacity of the CA matrix. Subsequent treatment of in-situ polymerized polyaniline (PANI) can enable the 3D fiber network to be coated with excellent conductive particles at the nanoscale without destroying the original fiber network. Using high-strength MWCNTs as CA matrix electrospinning fillers and growing PANI on the fiber surface by in-situ polymerization is a reasonable solution to the poor conductivity of CA and other polymer matrices, and can enrich the current research field of polymer-based electromagnetic shielding films. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a CA / MWCNTs / PANI electromagnetic shielding film and a preparation method thereof, using MWCNTs as fillers for electrospun CA fibers, and using CA / MWCNTs as templates to in-situ polymerize PANI to construct a three-dimensional conductive network structure. The present invention uses CA and MWCNTs to electrostatically co-spin, and uses a high-voltage electric field to construct a CA / MWCNTs polymerization template; through oxidative polymerization of aniline and an oxidant, PANI nanoparticles are in-situ coated and stacked on the surface of electrospun CA / MWCNTs fibers to obtain a CA / MWCNTs / PANI electromagnetic shielding network with enhanced conductivity and mechanical strength; the problem of insufficient conductivity of CA film when used alone is solved, and the mechanical properties and electromagnetic shielding effectiveness of the film are enhanced to meet more complex electromagnetic protection application scenarios.
[0006] Technical solution: To solve the above technical problems, the present invention provides a CA / MWCNTs / PANI electromagnetic shielding film and a preparation method thereof. The electromagnetic shielding film is composed of cellulose acetate (CA) and multi-walled carbon nanotubes (MWCNTs) as electrospinning precursors, combined with polyaniline (PANI) grown by in-situ polymerization; it comprises CA composite nanofibers CA / MWCNTs with MWCNTs as internal fillers, and PANI nanoparticles generated by aniline oxidative polymerization are coated and stacked on the surface of the CA / MWCNTs fiber network to form a three-dimensional conductive network.
[0007] The preparation method of the CA / MWCNTs / PANI electromagnetic shielding film of the present invention comprises the following steps:
[0008] (1) Preparation of electrospinning precursor: First, cellulose acetate powder was added to a mixed solution of dimethylacetamide and acetone, sealed with plastic wrap and stirred overnight until a clear and transparent colloid was formed. A certain amount of MWCNTs was added to the colloid, ultrasonicated for 30 minutes, and stirred to obtain a CA / MWCNTs electrospinning mixed precursor.
[0009] (2) Preparation of electrospun CA / MWCNTs fiber membrane: The CA / MWCNTs electrospinning mixed precursor obtained in step (1) was drawn into a syringe, vented and defoamed, and a 23G electrospinning needle was used to collect the fibers using a flat plate covered with aluminum foil. The positive voltage for spinning was 5 to 6 kV, the negative voltage was -0.20 to -0.30 kV, and the feed rate was 0.8 mL / h. After spinning, the CA / MWCNTs fiber membrane was peeled off from the aluminum foil and dried in a vacuum drying oven.
[0010] (3) Solution impregnation of CA / MWCNTs template: First, aniline monomer is added to a hydrochloric acid solution, and the CA / MWCNTs composite fiber membrane obtained in step (2) is cut into membrane sheets, which are then immersed in a mixed solution of aniline and hydrochloric acid and stirred in an ice bath at 0°C to obtain a solution-impregnated assembled template.
[0011] (4) In-situ polymerization of CA / MWCNTs / PANI film: First, ammonium persulfate was dissolved in a hydrochloric acid solution, and then the ammonium persulfate solution was dripped into the solution obtained in step (3) to impregnate the template, and then the polymerization reaction was carried out for a period of time in an ice bath at 0°C and magnetic stirring at 200 rpm. After the reaction was completed, the obtained CA / MWCNTs / PANI membrane was ultrasonically washed several times in distilled water, and then the membrane was dried in a vacuum drying oven to obtain a CA / MWCNTs / PANI electromagnetic shielding film.
[0012] In step (1), the mass ratio of dimethylacetamide:acetone:cellulose acetate is 6:3:1.
[0013] In step (1), the mass of MWCNTs added is 0.5wt%, 1wt%, and 1.5wt% of the mixed precursor.
[0014] In step (1), the ultrasonic treatment time of adding MWCNTs is 30 minutes, and the stirring time of adding MWCNTs is 2 hours.
[0015] In step (2), the electrospinning positive voltage is 5 to 6 kV, the negative voltage is -0.20 to -0.30 kV, and the feed rate is 0.8 mL / h.
[0016] The vacuum drying temperature in step (2) and step (4) is 30° C. and the drying time is 24 h.
[0017] The concentration of hydrochloric acid in step (3) and step (4) is 1 mol / L.
[0018] The molar ratio of the aniline monomer in step (3) to the ammonium persulfate in step (4) is 1:1.
[0019] The reaction time with ammonium persulfate in step (4) is 0.5 h, 1 h and 1.5 h.
[0020] Working principle: The electromagnetic shielding film of the present invention is composed of cellulose acetate (CA) and multi-walled carbon nanotubes (MWCNTs) as electrospinning precursors, combined with polyaniline (PANI) grown by in-situ polymerization; it contains CA composite nanofibers (CA / MWCNTs) with MWCNTs as internal fillers, and PANI nanoparticles generated by aniline oxidative polymerization are coated and stacked on the surface of the CA / MWCNTs fiber network to form a three-dimensional conductive network. The CA / MWCNTs fiber template is prepared by electrospinning under the action of a high-voltage electric field; the CA composite fiber membrane loaded with MWCNTs and the mixed solution containing aniline monomers are self-assembled by solution impregnation; the chemical in-situ oxidative polymerization method is used to form a micro-nano network structure in which PANI nanoparticles are in-situ coated on the CA / MWCNTs fiber. The CA / MWCNTs / PANI film of the present invention effectively shields electromagnetic waves. The formed conductive network is beneficial to the conduction loss of electromagnetic waves. The heterogeneous interface between the formed PANI nanoparticles and the CA / MWCNTs fibers is beneficial to the polarization loss of electromagnetic waves. At the same time, the MWCNTs filler and the polymerized PANI further increase the mechanical properties of the film, broadening the electromagnetic shielding application scenarios of the film.
[0021] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0022] (1) The present invention utilizes an electrospinning process to co-spin CA and MWCNTs, and forms a CA / MWCNTs fiber network composed of stacked nanofibers through a high-voltage electric field, thereby providing a template for the subsequent in-situ polymerization of PANI and also improving the mechanical properties of the film.
[0023] (2) The CA / MWCNTs fiber network was used as a template for in situ polymerization of PANI. The PANI nanoparticles were generated by the reaction of aniline monomer and oxidant, which were coated and stacked around the template, further enhancing the mechanical strength of the nanofibers. At the same time, the template was used as a support to form a PANI conductive network structure with enhanced conductivity.
[0024] (3) The network structure with enhanced conductivity provides a path for electron transport, which promotes the attenuation of the energy of electromagnetic waves entering the film; at the same time, the heterogeneous interface at the junction of PANI and the fiber causes the dipole to produce polarization losses. CA / MWCNTs / PANI can effectively dissipate the energy of electromagnetic waves entering the film, promote conduction losses and interface polarization losses, and improve the ability to absorb electromagnetic waves. Compared with other electromagnetic shielding materials, the CA / MWCNTs / PANI electromagnetic shielding film of the present invention has an in-situ PANI-coated fiber structure with enhanced conductivity, has the advantages of simple and feasible process, small thickness, etc., has a reliable conductive path and heterogeneous interface, and realizes electromagnetic shielding.
[0025] (4) The electromagnetic shielding film has good mechanical properties, can effectively shield electromagnetic waves, and has the advantages of conductivity and hydrophilicity. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a SEM image of the CA / MWCNTs / PANI electromagnetic shielding film of the present invention;
[0027] Figure 2 is a SEM image of the CA / MWCNTs film of the present invention;
[0028] Figure 3 The electromagnetic shielding performance of the CA / MWCNTs / PANI electromagnetic shielding film prepared in Example 1 of the present invention;
[0029] Figure 4 Schematic diagram of the microstructure of the CA / MWCNTs / PANI electromagnetic shielding film of the present invention. DETAILED DESCRIPTION
[0030] Embodiment 1:
[0031] The CA / MWCNTs / PANI electromagnetic shielding film of the invention is composed of CA composite fibers with MWCNTs as fillers and in-situ coated PANI, and has an electromagnetic shielding film with an enhanced conductive network.
[0032] The preparation method of the CA / MWCNTs / PANI electromagnetic shielding film of the present invention comprises the following steps:
[0033] (1) Preparation of electrospinning precursor: First, add 1 g of cellulose acetate powder to a mixed solution of 6 g of dimethylacetamide and 3 g of acetone, seal with plastic wrap and stir overnight until a clear and transparent colloid is formed. Add a certain amount of MWCNTs to the colloid, ultrasonicate for 30 min, and stir at 500 rpm for 2 h to obtain a CA / MWCNTs electrospinning mixed precursor.
[0034] (2) Electrospinning CA / MWCNTs fiber membrane: The CA / MWCNTs electrospinning mixed precursor obtained in step (1) was pumped into a 5 mL syringe, vented and defoamed, and a 23G electrospinning needle was used to collect the fibers using a flat plate covered with aluminum foil. The collection distance was 12 cm, the spinning positive voltage was 5 kV, the negative voltage was -0.20 kV, and the feed rate was 0.8 mL / h. After spinning, the CA / MWCNTs fiber membrane was peeled off from the aluminum foil and dried in a vacuum drying oven at 30°C for 24 h.
[0035] (3) Solution impregnation of CA / MWCNTs template: First, add 1 mL of aniline monomer into 10 mL of 1 mol / L hydrochloric acid solution, cut the CA / MWCNTs composite fiber membrane obtained in step (2) into a membrane sheet with a length of 3 cm and a width of 2 cm, and then immerse it in a mixed solution of aniline and hydrochloric acid, and stir in an ice bath at 0°C for 1 h to obtain a solution-impregnated assembled template.
[0036] (4) In-situ polymerization of CA / MWCNTs / PANI film: First, 2.505 g of ammonium persulfate was dissolved in 10 mL of 1 mol / L hydrochloric acid solution, and then the ammonium persulfate solution was dripped into the solution obtained in step (3) to impregnate the template, and then the polymerization reaction was carried out for a certain period of time in an ice bath at 0°C and magnetic stirring at 200 rpm. After the reaction was completed, the obtained CA / MWCNTs / PANI membrane was ultrasonically washed 3 times in distilled water, and the single ultrasonic washing time was 2 min. Then the membrane was dried in a vacuum drying oven at 30°C for 24 h to obtain a CA / MWCNTs / PANI electromagnetic shielding film.
[0037] Embodiment 2:
[0038] The preparation method of the CA / MWCNTs / PANI electromagnetic shielding film of the present invention comprises the following steps:
[0039] (1) Preparation of electrospinning precursor: First, 1 g of cellulose acetate powder was added to a mixed solution of 6 g of dimethylacetamide and 3 g of acetone, sealed with plastic wrap and stirred overnight until a clear and transparent colloid was formed. A certain amount of MWCNTs was added to the colloid, ultrasonicated for 30 min, and stirred at 500 rpm for 2 h to obtain a CA / MWCNTs electrospinning mixed precursor.
[0040] (2) Electrospinning CA / MWCNTs fiber membrane: The CA / MWCNTs electrospinning mixed precursor obtained in (1) was pumped into a 5 mL syringe, vented and defoamed, and a 23G electrospinning needle was used to collect the fibers using a flat plate covered with aluminum foil. The collection distance was 12 cm, the spinning positive voltage was 5.5 kV, the negative voltage was -0.30 kV, and the feed rate was 0.8 mL / h. After spinning, the CA / MWCNTs fiber membrane was peeled off the aluminum foil and dried in a vacuum drying oven at 30°C for 24 h.
[0041] (3) Solution impregnation of CA / MWCNTs template: First, add 1 mL of aniline monomer into 10 mL of 1 mol / L hydrochloric acid solution, cut the CA / MWCNTs composite fiber membrane obtained in step (2) into a membrane sheet with a length of 3 cm and a width of 2 cm, and then immerse it in a mixed solution of aniline and hydrochloric acid, and stir in an ice bath at 0°C for 1 h to obtain a solution-impregnated assembled template.
[0042] (4) In-situ polymerization of CA / MWCNTs / PANI film: First, 2.505 g of ammonium persulfate was dissolved in 10 mL of 1 mol / L hydrochloric acid solution, and then the ammonium persulfate solution was slowly dripped into the solution obtained in step (3) to impregnate the template, and then the polymerization reaction was carried out for a period of time in an ice bath at 0°C and magnetic stirring at 200 rpm. After the reaction was completed, the obtained CA / MWCNTs / PANI membrane was ultrasonically washed 3 times in distilled water, and the single ultrasonic washing time was 2 min. Then the membrane was dried in a vacuum drying oven at 30°C for 24 h to obtain a CA / MWCNTs / PANI electromagnetic shielding film.
[0043] like Figure 1 As shown in the figure, the SEM image of the CA / MWCNTs / PANI electromagnetic shielding film prepared by the present invention. PANI is successfully grown in situ on the CA / MWCNTs template, and the fiber diameter is significantly improved; PANI is coated on the original CA / MWCNTs fiber, and nano-scale particles grow around it; the local manifestation is a large number of particles stacked, and the stacking is based on the original CA / MWCNTs as a template, which ensures the conductive path of the composite film.
[0044] like Figure 2 The CA / MWCNTs film prepared by the present invention is shown in Figure 1. CA is mixed with MWCNTs precursors by electrospinning for co-spinning, and the mixture colloid is stretched and refined into nano-scale fibers by a high voltage electric field. The fibers are bent and split in the electric field and finally stacked into a network structure, providing a template for in-situ polymerization of PANI.
[0045] pass Figure 3 It was concluded that the electromagnetic shielding film had the best electromagnetic shielding performance when the polymerization time was 1.5h, and its corresponding electromagnetic shielding performance was 33dB.
[0046] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A CA / MWCNTs / PANI electromagnetic shielding film, characterized in that: The electromagnetic shielding film is composed of cellulose acetate CA and multi-walled carbon nanotubes MWCNTs as electrospinning precursors, combined with polyaniline PANI grown by in-situ polymerization; it includes CA composite nanofibers CA / MWCNTs with MWCNTs as internal fillers, and PANI nanoparticles generated by aniline oxidative polymerization are coated and stacked on the surface of the CA / MWCNTs fiber network to form a three-dimensional conductive network.
2. A method for preparing the CA / MWCNTs / PANI electromagnetic shielding film according to claim 1, characterized in that: The following steps are involved: (1) preparing an electrospinning precursor: adding cellulose acetate powder to a dimethylacetamide and acetone solution, mixing the mixture, stirring the mixture magnetically until the mixture is dissolved to form a colloid, then adding MWCNTs for ultrasonic treatment, and then stirring the mixture to obtain a CA / MWCNTs electrospinning precursor; (2) Preparing electrospun CA / MWCNTs composite fiber membrane: The CA / MWCNTs electrospinning precursor obtained in step (1) is drawn into a syringe, the air is exhausted and defoamed, an electrospinning needle is matched, the positive and negative voltages and feed speed of the electrospinning are adjusted, and the fibers are collected on a flat plate covered with aluminum foil. After the spinning is completed, the CA / MWCNTs fiber membrane is peeled off from the aluminum foil and vacuum dried to obtain a CA / MWCNTs composite fiber membrane; (3) Solution impregnation of CA / MWCNTs template: The cut CA / MWCNTs composite fiber membrane in step (2) is immersed in a mixed solution of hydrochloric acid containing aniline monomer, and stirred in an ice bath to obtain a solution-impregnated assembled template; (4) In situ polymerization of CA / MWCNTs / PANI film: The impregnated assembly template obtained in step (3) is reacted with a mixed solution of ammonium persulfate and hydrochloric acid in an ice bath environment. After the reaction is completed, it is ultrasonically washed with distilled water for multiple times, and then vacuum dried to obtain a CA / MWCNTs / PANI electromagnetic shielding film.
3. The method for preparing the CA / MWCNTs / PANI electromagnetic shielding film according to claim 2, characterized in that: In the step (1), the mass ratio of dimethylacetamide:acetone:cellulose acetate is 6:3:
1.
4. The method for preparing the CA / MWCNTs / PANI electromagnetic shielding film according to claim 2, characterized in that: In step (1), the mass of MWCNTs added is 0.5wt%, 1wt%, and 1.5wt% of the mixed precursor.
5. The method for preparing the CA / MWCNTs / PANI electromagnetic shielding film according to claim 2, characterized in that: In step (1), the ultrasonic treatment time of adding MWCNTs is 30 minutes, and the stirring time of adding MWCNTs is 2 hours.
6. The method for preparing the CA / MWCNTs / PANI electromagnetic shielding film according to claim 2, characterized in that: In step (2), the electrospinning positive voltage is 5 to 6 kV, the negative voltage is -0.20 to -0.30 kV, and the feed rate is 0.8 mL / h.
7. The method for preparing the CA / MWCNTs / PANI electromagnetic shielding film according to claim 1, characterized in that: The vacuum drying temperature in step (2) and step (4) is 30° C. and the drying time is 24 h.
8. The method for preparing the CA / MWCNTs / PANI electromagnetic shielding film according to claim 1, characterized in that: The concentration of hydrochloric acid in step (3) and step (4) is 1 mol / L.
9. The method for preparing the CA / MWCNTs / PANI electromagnetic shielding film according to claim 1, characterized in that: The molar ratio of the aniline monomer in step (3) to the ammonium persulfate in step (4) is 1:
1.
10. The method for preparing the CA / MWCNTs / PANI electromagnetic shielding film according to claim 1, characterized in that: The reaction time with ammonium persulfate in step (4) is 0.5 h, 1 h and 1.5 h.
Citation Information
Cited By
Polyaniline / polyisophthaloyl metaphenylene diamine electromagnetic shielding material as well as preparation method and application thereof
CN121496749A